Explaining child malnutrition in developing countries: a cross-country analysis - Smith, Lisa C.; Haddad, Lawrence James (International Food Policy Research Institute, 1999)
One in three pre-school children in the developing world is undernourished. As a consequence, their human rights are violated. In addition, they are more likely to have impaired immune systems, poorer cognitive development, lower productivity as adults, and greater susceptibility to diet-related chronic diseases such as hypertension and coronary heart disease later in life. Undernourished female preschoolers are likely to grow into undernourished young women who are more likely to give birth to babies who are undernourished even before they are born, thus perpetuating the inter-generational transmission of deprivation. Reducing these unacceptably high numbers remains a tremendous challenge to public policy. As a guide to the direction of future efforts, this research report examines the success of the efforts of the past 25 years to reduce preschooler undernutrition. The report uses an econometric model to identify the factors associated with the reduction in undernutrition. The formulation of the econometric model is guided by the widely accepted food-care-health conceptual model of child growth. The contributions of both underlying and basic determinants to reductions in undernutrition are assessed using the model. The potential of these factors to further reduce undernutrition is evaluated in a region-by-region priority-setting exercise. In addition, projections of child nutrition are made under various scenarios to the year 2020. What will it take to dramatically reduce undernutrition in the next 20 years? The report attempts some broad answers to these questions...(Forward by Per Pinstrup-Andersen)